Variably protease‐sensitive prionopathy mimicking frontotemporal dementia. Issue 2 (7th March 2019) - Aizpurua, Miren; Selvackadunco, Sashika; Yull, Helen; Kipps, Christopher M.; Ironside, James W.; Bodi, Istvan
Abstract : Sporadic prion diseases are fatal neurodegenerative disorders characterized clinically by rapidly progressive dementia and myoclonus. Variably protease‐sensitive prionopathy (VPSPr) is a recently identified sporadic human prion disorder that may present with a lengthy atypical clinical history. Here, we describe a case of VPSPr in a patient with a long history of suspected frontotemporal dementia (FTD). A 61‐year‐old man presented with speech difficulties, including naming objects and constructing multipart sentences, while there was no difficulty in comprehension. Movement abnormalities included slightly jerky pursuit, minor dysmetria of saccades and brisk reflexes. There was no family history of dementia. Later he developed swallowing difficulties and the possibility of FTD with motor neuron disease was suspected. He died at the age of 71 and his brain was donated to the London Neurodegenerative Diseases Brain Bank. The brain (1004 g) showed mild to moderate atrophy, predominantly in the frontal lobe. Histology revealed moderate spongiform microvacuolation mostly affecting the frontal and parietal cortices, but also present focally in the basal ganglia and the cerebellum. Only mild Alzheimer pathology was found by extensive immunohistochemistry, in keeping with BrainNet Europe stage II. Trans‐activation response DNA‐binding protein 43 kDa and α‐synuclein immunostains were negative. Immunostaining for prion protein (PrP) showed granular/synaptic positivity in a patchy distribution, mainly within the deeper cortex, and also revealed microplaques in the cerebellum and basal ganglia. Western blotting confirmed a low molecular weight protease‐resistant PrP band with a faint ladder‐like pattern in the absence of types 1 and 2 isoforms. These features are diagnostic of VPSPr. VPSPr can mimic various neurodegenerative conditions; diagnosis requires both PrP immunohistochemistry and Western blotting. The presence of patchy spongiform change in the absence of other neurodegenerative pathology should raise suspicion of VPSPr, even in elderly patients with a lengthy clinical history.